2017
DOI: 10.1332/239788217x15084960724368
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation? The challenges of measuring informal care among children and young people

Abstract: According to data in the UK Census of Population, the number of young carers aged between 5 and 17 years old increased substantially between 2001 and 2011. By 2011, 2.1% of young people aged 5 to 17 years in England and Wales were young carers (ONS, 2013). The comparative figure for Scotland was 2% (NRS, 2011), while for Northern Ireland it was 2.8% (NISRA, 2011). Prevalence estimates for young carers vary widely across different surveys, however, for several reasons. The first main issue relates to question w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…For instance, the 2016 Australia Census found that 5.6% of those aged 15–24 years reported informal care, a slight increase from 5.0% in 2006. These few studies are based on census data from only two time-points, with statistics that might rely on parents’ disclosure of the caregiving role of their children which can underestimate care prevalence among young people [ 17 , 18 ]. Therefore, to date, no studies have provided an overview of the annual prevalence of caregiving among young people over several years using a survey which, by design, collects information on different aspects of participants’ lives directly from each participant.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the 2016 Australia Census found that 5.6% of those aged 15–24 years reported informal care, a slight increase from 5.0% in 2006. These few studies are based on census data from only two time-points, with statistics that might rely on parents’ disclosure of the caregiving role of their children which can underestimate care prevalence among young people [ 17 , 18 ]. Therefore, to date, no studies have provided an overview of the annual prevalence of caregiving among young people over several years using a survey which, by design, collects information on different aspects of participants’ lives directly from each participant.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of prevalence often use various definitions of young carers, age ranges, samples, methods of research and instruments to measure outcomes (Aldridge, 2017;Kavanaugh et al, 2016;Stamatopoulos, 2015). Therefore, reliable cross-national prevalence and outcome data are rare (Aldridge, 2017;Kelly, Devine, & McKnight, 2017;Leu & Becker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the 2016 Australia Census found that 5.6% of those aged 15-24 years reported informal care, a slight increase from 5.0% in 2006. These few studies are based on census data from only two time-points, with statistics that might rely on parents' disclosure of the caregiving role of their children which can underestimate care prevalence among young people (Kelly, Devine and McKnight 2017;. Therefore, to date, no studies have provided an overview of the annual prevalence of caregiving among young people over several years using a survey which, by design, collects information on different aspects of participants' lives directly from each participant.…”
Section: Prevalence Of Care Among Young Peoplementioning
confidence: 99%